The Role of Eye Gaze in Regulating Turn Taking in Conversations: A Systematized Review of Methods and Findings - Degutyte, Ziedune; Astell, Arlene (Frontiers in Psychology, 2021)
Eye gaze plays an important role in communication but understanding of its actual function or functions and the methods used to elucidate this have varied considerably. This systematized review was undertaken to summarize both the proposed functions of eye gaze in conversations of healthy adults and the methodological approaches employed. The eligibility criteria were restricted to a healthy adult population and excluded studies that manipulated eye gaze behaviour. A total of 29 articles - quantitative, qualitative and mixed methods were returned, with a wide range of methodological designs. The main areas of variability related to number of conversants, their familiarity and status, conversation topic, data collection tools – video and eye tracking - and definitions of eye gaze. The findings confirm that eye gaze facilitates turn yielding, plays a role in speech monitoring, prevents and repairs conversation breakdowns and facilitates intentional and unintentional speech interruptions. These findings were remarkably consistent given the variability in methods across the 29 articles. However, in relation to turn initiation, the results were less consistent, requiring further investigation. This review provides a starting point for future studies to make informed decisions about study methods for examining eye gaze and selecting variables of interest.